PERAN KONSELING ISLAM DALAM PENURUNAN STRES PADA MAHASISWA (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2023)
This study aims to determine the effect of Islamic counseling on reducing stress in college students.This research is a quantitative research with a quasi-experimental approach. Respondents weretaken using convenience sampling. The focus of this research is on the level student anxiety inlearning. The indicators include: conveying objectives experiments, preparing experimental materials,namely modules and materials, carrying out experiments using an Islamic counseling approach,recording and measuring experimental results. The target and at the same time the subject of thestudy were Psychology Undergraduate Students at Sahid University, Surakarta totaling 7 people. Thetreatment was given using an Islamic counseling approach. Stress was measured using a stress scale,then pretest and posttest data were obtained. Test the hypothesis used parametric statistics with ttest, for normally distributed data. Non-parametric statistics with a two-sample columnogrorovsminov test, for data that is not normally distributed. The results of this study indicate that Islamiccounseling has no effect on reducing stress on students in dealing with learning.